Obtenção de nanomateriais e hidrogéis nanocompósitos a base de poliacrilamida: aplicações em controle de conformidade de reservatórios de petróleo e remediação de corante e microplásti cos - Sthéfany Zaida Silva do Amparo (2023)
This work aims to apply nanomaterials in conjunction with polymeric matrices to contribute to reducing environmental impact in three different research lines: i) photodegradation of microplastics; ii) hydrogels for dye adsorption; iii) hydrogels for enhanced oil recovery (EOR). Titanium dioxide (TiO2) nanoparticles were scaled up for the photodegradation of polypropylene (PP) and polystyrene (PS) microplastics. Photodegradation led to the formation of carbonyl groups and cross-linking, as observed through thermal analysis. Thus, these results indicate that simultaneous reactions occur during microplastic photodegradation. Nanocomposite hydrogels based on polyacrylamide (PAM) were reinforced with TiO2, oxidized carbon nanotubes (CNT-ox), and graphene oxide (GO) for various applications. Functionalization through microwave-assisted GO amination with diethylenetriamine (DETA) was performed, followed by the synthesis of nanocomposite hydrogels (GO-DETA/PAM) for dye adsorption. GO-DETA sheets played a crucial role as a cross-linking agent during PAM polymerization, resulting in a maximum adsorption capacity of 205.4 mg g-1. In the hydrogel line, pre-formed gel particles (PPG) were produced as nanocomposites with TiO2, GO, and CNT-ox synthesized (0.1% w/w in the monomer) via microwave radiation. These hydrogels were evaluated for their application in EOR. Apparent viscosity results showed values below 30 mPa·s at shear rates similar to injection well conditions (< 300 s-1) for most systems containing 0.5%, 1.0%, and 2.0% PPG by mass in saline water, indicating their potential application in high-salinity reservoirs. However, further studies are required. In conclusion, this work explored the potential of nanotechnology in three fields related to environmental issues, encompassing research in all necessary stages: i) optimized nanomaterial synthesis; ii) material production incorporating nanomaterials; iii) comprehensive characterization of system components; iv) physicochemical testing of properties of interest, such as adsorption, viscosity, photodegradation, among others.